An empirical force field for the simulation of the vibrational spectroscopy of carbon nanomaterials - Tailor, Pritesh M.; Wheatley, Richard J.; Besley, Nicholas A. (Elsevier, 2017)
An empirical force field for carbon based upon the Murrell-Mottram potential is developed for the calculation of the vibrational frequencies of carbon nanomaterials. The potential is reparameterised using data from density functional theory calculations through a Monte-Carlo hessian-matching approach, and when used in conjunction with the empirical bond polarisability model provides an accurate description of the non-resonant Raman spectroscopy of carbon nanotubes and graphene. With the availability of analytical first and second derivatives, the computational cost of evaluating harmonic vibrational frequencies is a fraction of the cost of corresponding quantum chemical calculations, and makes the accurate atomistic vibrational analysis of systems with thousands of atoms possible. Subsequently, the non-resonant Raman spectroscopy of carbon nanotubes and graphene, including the role of defects and carbon nanotube junctions is explored.